PENDIDIKAN TASAWUF DI PONDOK MODERN DARUSSALAM GONTOR - M Ihsan Dacholfany (Nizham Jurnal Studi Keislaman, 2015)
Sufism and schools have a fairly close relationship. In the expansion, it can be said boarding house development therapy Sufi teachings today. The development is due to be supported by several factors, one of which is the teaching of the yellow book. In the world of boarding, yellow book is thing that can not be separated in learning. The yellow book is a book or a book written by the classical scholars were largely Sufi teachings. Then simultaneously, the Sufi teachings can be tranfered to study of books in several classes.This text is to reveal the relationship the Gontor boarding school with Sufi teachings that developed in the Islamic world. Actually, in Gontor activity, elements of Sufism can be detected through the everyday activities of the students, such as: accepting state (resigned), simplicity, not overbearing and so forth. At Gontor boarding school, attitude Sufism is called with the five souls. Where attitudes were reflected as: Concept shidiq, shabru, ukhuwah, zuhud, qana’ah amanah, ikhlas, tawakkal.